IMPLEMENTASI MANAJEMEN PENGEMBANGAN KARAKTER MELALUI EDUKASI NILAI PERDAMAIAN PADA KEGIATAN PEACE POSTER CONTEST - Brigida Endah Nuraeni; Edi Sumarya (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
This community service program aims to implement character development management by promoting the values of peace, tolerance, and humanity among young participants through the Peace Poster Contest organized by Lions Clubs International District 307-A1. The activity adopts an educational and participatory approach by integrating human resource development management functions, including planning, implementation of value-based learning, and evaluation through poster assessment, feedback provision, and observation of participants’ comprehension. The participants are students aged 7–13 years, representing a critical stage in character formation as part of early human resource development. The findings indicate that participants are able to creatively convey peace-related values through visual media and demonstrate improved understanding of tolerance and harmonious coexistence. Furthermore, the involvement of academics as judges enhances the managerial aspect of the program through structured and educational evaluation. Therefore, this activity confirms that the application of character development management based on peace education is effective in fostering character formation and supporting human resource development oriented toward humanitarian values.